2012
DOI: 10.1002/adma.201201319
|View full text |Cite
|
Sign up to set email alerts
|

Nematic Director‐Induced Switching of Assemblies of Hexagonally Packed Gold Nanorods

Abstract: Self‐assembled disc‐shaped clusters of hexagonally packed, thiol‐functionalized gold nanorods are prepared and dispersed in thermotropic nematic liquid crystals. The resultant hybrid complex fluids exhibit colloidal anisotropy with very high orientational order and are characterized by SAXS as shown in the figure. Precise, reconfigurable control of the cluster orientation at very low electric field strengths (0.18 V μm−1) is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…A related example of such GNR reorientation in electric fi elds was recently disclosed by Richardson and co-workers for shortrange ordered hexagonally packed GNR suspended in a nematic liquid crystal (5CB). [ 40 ] The key difference in the present work is that the GNRs assemble into nematic and to some degree smectic-type arrays with only a miniscule amount of free liquid crystal molecules (about 1% by weight). Hence, the free liquid crystal acts here as the dopant (or suspended entity promoting attractive interactions between GNRs) in contrast to GNR suspensions investigated by others.…”
Section: D)mentioning
confidence: 99%
“…A related example of such GNR reorientation in electric fi elds was recently disclosed by Richardson and co-workers for shortrange ordered hexagonally packed GNR suspended in a nematic liquid crystal (5CB). [ 40 ] The key difference in the present work is that the GNRs assemble into nematic and to some degree smectic-type arrays with only a miniscule amount of free liquid crystal molecules (about 1% by weight). Hence, the free liquid crystal acts here as the dopant (or suspended entity promoting attractive interactions between GNRs) in contrast to GNR suspensions investigated by others.…”
Section: D)mentioning
confidence: 99%
“…In previous work, we have shown that hexagonally packed clusters of gold nanorods (GNRs), modified with short alkyl thiol coatings, can be remarkably well directed by nematic liquid crystal hosts. [12]. Recently, Liu et al [13] achieved orientational control of GNRs as single particles which allowed control of the anisotropic plasmon resonance absorption to be demonstrated.…”
Section: Introductionmentioning
confidence: 97%
“…[41, 42] However, a serious drawback met in the use of most of thermotropicliquid crystals corresponds to the induced aggregation of thenanorods. [36,[43][44] This aggregation is due to the distortions and disorder induced in the liquid crystal around most of the nanoparticles, which become reduced if the nanoparticles are aggregated. [36,45] In nematic liquid crystals, the best method to prevent aggregation of nanorods is to graft specific ligandsaround the nanorodsin order to allow for a weak anchoring of the liquid crystal molecules.…”
mentioning
confidence: 99%